Penerapan Metode CPI dan ROC Dalam Keputusan Pemilihan Perioritas Pembangunan Infrastruktur Desa - Fransin Romualdus Tampubolon (BEES: Bulletin of Electrical and Electronics Engineering, 2021)
Village development is part of the government's program for village empowerment efforts. Determination of priorities for village infrastructure development has certain criteria in accordance with the policies of the local village apparatus. This is done with the hope that village infrastructure development can be more targeted and equitable. a decision is needed to determine priorities for village infrastructure development, in determining village infrastructure development decisions, it is still carried out by voting often, more important developments must be delayed because they lost votes. Therefore, the decision support system (Decision Support System) can assist the village government in determining the priority of drsa infrastructure development. The methods used to determine the priority of village infrastructure development are Rank Order Centroid (ROC) and CPI. Where each alternative will be ranked to get development priorities in accordance with the criteria determined by the village. With the construction of a decision support system for determining village infrastructure development priorities using the ROC and CPI methods, it is expected to provide convenience, accuracy and speed for determining development priorities in Wonosari village.